GARP Outperformance Over Growth: Towards an Old and a New Paradigm - Bossens, Frederik (Digital Repository of Theses, 2024)
Value investing and growth investing are two forms of investing. Previous research demonstrates that value outperforms growth. This paradigm has been broadly supported in literature. GARP is another form of investment that was forgotten in the paradigm. GARP needs to be introduced in that paradigm. According to literature, it is expected that GARP will outperform growth but not value. Therefore, the purpose of this study is to complete the paradigm by demonstrating GARP’s outperformance over growth and underperformance compared to value. However, researchers have noticed large-scale changes in performance that started occurring around the Great Financial Crisis. Growth seems to have started outperforming value, in contradiction to the traditional value outperforming growth paradigm. However, there are still mixed findings around the world on whether growth or value outperforms. A global model for outperformance is therefore needed. A major part of this research is aimed at testing the changes in outperformance, and setting up GARP’s place in the new paradigm, where growth now seems to outperform value. For the first period, it turns out that value and GARP outperform growth about as much in the period before the GFC, both in developing and emerging markets. However, there is no outperformance of growth, value, nor GARP in the second period, except in emerging markets. It is evident that the old paradigm of value outperforming growth in the period before the GFC, can be completed by introducing a GARP strategy that will be roughly as strong, in outperforming growth, as value. However, for the period starting in the GFC, tech companies performance was flat for all strategies in developed markets. However, in emerging markets, there are still huge profits to be made by tangible asset based value and GARP companies, the evidence shows the outperformance of GARP and the performance of value that is similar to the old paradigm. Hence, it becomes more important for investors to move towards emerging markets to have statistical backing. These tangible asset based value and GARP companies form the basis for what can be called the new paradigm of outperformance of GARP and value over growth, that has shifted to the emerging markets. In this study, all of this was proven by a battery of nineteen tests, with the testing of the outperformance as the most important test, while others, including paired t-tests, correlation analyses, F-tests, covariance tests, Phillips-Oullaris tests, and outliers tests, were used to provide more knowledge and reliability to the findings.